Neglected and Emerging Tropical Diseases in South and Southeast Asia and Northern Australia - Khin Saw Aye (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This Special Issue focuses on recent research on the important emerging and neglected tropical diseases (NTDs) in South and South East Asia and Northern Australia. This region stretches from Afghanistan in the west to Papua New Guinea in the east, and includes the Indian subcontinent, mainland South-East Asia (Indo China), maritime South East Asia, and the tropical regions of Australia. Many of these areas are highly endemic for important NTDs and emerging infectious diseases including lymphatic filariasis, leprosy, soil-transmitted helminthiases (hookworm, Trichuris, Ascaris, and Strongyloides), food-borne trematodiases, schistosomiasis, dengue/chikungunya/zika, leptospirosis, meloidosis, scabies, trachoma, and yaws. Several of these diseases are targeted for elimination or enhanced control by the World Health Organization in the next 5 to 10 years, although some have chronic lasting sequelae needing lifelong management. Control methods used include preventive chemotherapy, enhanced screening and treatment, intensified disease management, vector control, interruption of human to animal transmission, environmental/sanitation improvements and disability prevention/mitigation.